2018
DOI: 10.1038/s41598-018-27539-2
|View full text |Cite
|
Sign up to set email alerts
|

Further dissection of QTLs for salt-induced stroke and identification of candidate genes in the stroke-prone spontaneously hypertensive rat

Abstract: We previously revealed that two major quantitative trait loci (QTLs) for stroke latency of the stroke-prone spontaneously hypertensive rat (SHRSP) under salt-loading were located on chromosome (Chr) 1 and 18. Here, we attempted further dissection of the stroke-QTLs using multiple congenic strains between SHRSP and a stroke-resistant hypertensive rat (SHR). Cox hazard model among subcongenic strains harboring a chromosomal fragment of Chr-1 QTL region showed that the most promising region was a 2.1 Mbp fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Additionally, expression of CXCL17 is co-regulated with other proangiogenic molecules as IL-8, GRO-1 and VEGF in samples from lung, breast and esophageal cancers [20]. Finally, CXCL17 is one of the most important genes mutated within specific genetic loci of stroke susceptibility in stroke-prone spontaneously hypertensive rats, a murine model of spontaneous cerebral hemorrhage suggesting a potential participation of this chemokine in the maintenance of vascular structure [38].…”
Section: Angiogenic Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, expression of CXCL17 is co-regulated with other proangiogenic molecules as IL-8, GRO-1 and VEGF in samples from lung, breast and esophageal cancers [20]. Finally, CXCL17 is one of the most important genes mutated within specific genetic loci of stroke susceptibility in stroke-prone spontaneously hypertensive rats, a murine model of spontaneous cerebral hemorrhage suggesting a potential participation of this chemokine in the maintenance of vascular structure [38].…”
Section: Angiogenic Effectmentioning
confidence: 99%
“…Angiogenic activity of CXC chemokines is dependent on the presence or absence of the ELR motif [10,37]. Although the ELR motif has not been described in CXCL17, functionally it behaves as a member of the group of angiogenic factors [20,23,38]. In fact, several human endothelial cell lines such as human microvascular endothelial cells (HMVEC), sephranose vascular endothelial cells (SPVEC) and human umbilical vascular endothelial cells (HUVEC) express higher levels of CXCL17 during proliferation or tube formation [20].…”
Section: Angiogenic Effectmentioning
confidence: 99%
“…SHRSP/Izm rats were provided by the Disease Model Cooperative Research Association (Kyoto, Japan). Subcongenic strains harboring a SHR/Izm-derived chr-1 fragment on the genetic background of SHRSP/Izm were obtained as described previously [ 3 , 4 ]. Briefly, Pr1.10 females (termed SHRSP.SHR-( D1Mgh5 - D1Got87 )/Izm, NBRP Rat No.0709) were backcrossed with a SHRSP/Izm male, and the resulting F1 rats were intercrossed to obtain pups of the F2 generation.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we identified major quantitative trait loci (QTL) for salt-induced stroke on chromosome (chr) 1 and 18 by linkage analysis [ 3 ]. In a recent study using reciprocal congenic strains for the stroke QTLs [ 4 ], we identified six candidate genes (Cbl protooncogene C, Cblc ; C-X-C motif chemokine ligand 17, Cxcl17 ; zinc finger protein 45-like, LOC102548695 , Zfp45L ; ETHE1 persulfide dioxygenase, Ethe1 ; capicua transcriptional repressor, Cic ; and carcinoembryonic antigen-related cell adhesion molecule 19, Ceacam 19 ) in a 3-Mbp fragment on chr 1 covered by a SHRSP-based congenic strain, Pr1.31. However, as the annotated molecular functions of these six genes were not directly involved in the development of stroke, it is essential to explore their functional roles in the development of stroke or to reduce the number of candidate genes further (ideally, to only one).…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression of Col1α-1 , Tgf- β , α-Sma ( markers for fibrosis), and Kim-1 ( a marker for tubular injury) was determined in the kidney by quantitative RT-PCR as described previously [15, 16]. The primers used are as follows: α-Sma : GAGATCTCACCGACTACCTCATGA (forward), TCATTTTCAAAGTCCAGAGCGACA (reverse), Tgf- β : ATCCATGACATGAACCGACCCT (forward), GCCGTACACAGCAGTTCTTCTC (reverse), Col1α -1 : ACATGTTCAGCTTTGTGGACCTC (forward), TCAGGTTTCCACGTCTCACCA (reverse), Kim-1 : GGAGCAGCGGTCGATACAACATA (forward), TCTCCACTCGGCAACAATACAGAC (reverse).…”
Section: Methodsmentioning
confidence: 99%